Health and climate benefits of offshore wind facilities in the Mid-Atlantic United States. (14th July 2016) - Buonocore, Jonathan J; Luckow, Patrick; Fisher, Jeremy; Kempton, Willett; Levy, Jonathan I
Abstract: Electricity from fossil fuels contributes substantially to both climate change and the health burden of air pollution. Renewable energy sources are capable of displacing electricity from fossil fuels, but the quantity of health and climate benefits depend on site-specific attributes that are not often included in quantitative models. Here, we link an electrical grid simulation model to an air pollution health impact assessment model and US regulatory estimates of the impacts of carbon to estimate the health and climate benefits of offshore wind facilities of different sizes in two different locations. We find that offshore wind in the Mid-Atlantic is capable of producing health and climate benefits of between $54 and $120 per MWh of generation, with the largest simulated facility (3000 MW off the coast of New Jersey) producing approximately $690 million in benefits in 2017. The variability in benefits per unit generation is a function of differences in locations (Maryland versus New Jersey), simulated years (2012 versus 2017), and facility generation capacity, given complexities of the electrical grid and differences in which power plants are offset. This work demonstrates health and climate benefits of offshore wind, provides further evidence of the utility of geographically-refined modeling frameworks, and yields quantitative insights that would allow for inclusion of both climate and public health in benefits assessments of renewable energy.